Gynogenesis in Persian sturgeon (Acipenser persicus) and beluga (Huso huso) - Pourkazemi, M.; Mohseni, M.; Alipour, A.R.; Nowruzfashkhami, M.R.; Hassanzadeh Saber, M.; Bahmani, M.; Rezvani Gilkolaei, S. (Iranian Fisheries Science Research Institute, 2010)
The objective of the present study was to determine the possible production of Persian sturgeon (Acipenser persicus) and Beluga (Huso huso) gynogen/triploids and also to determine the most appropriate type of thermal shock and the duration of induced shock after fertilization. Persian sturgeon and Beluga spawners were collected from Guilan's sturgeon catch stations and transported to the Shahid Beheshti sturgeon hatchery for artificial breeding and restocking programs. Ovulated eggs and sperms were collected based on common procedures in hatcheries. In order to separate the seminal fluids and dilute the milts, sperms were centrifuged at 6000 rpm for 20 min. and seminal fluids stored in refrigerator for further use. Sperm motility was investigated. In order to determine the best duration for radiation, the milt was diluted (1:9) with immobilizing solution. Samples of diluted milt were placed for UV irradiation (UV lamp model UVG-54, 254 nm, made by UVP America) for 0.5, 1, 1.5, 1.45, 2, to 5 min. The motility of radiated sperms and controls were examined under the light microscope and the motility curve was drawn. For application of thermal shock two types of heat shock (32, 34 and 37°C) and cold shock (0±1°C) were used for duration of 2.5 and 60 min respectively. Both thermal shock were applied at 12, 15, 18 min after fertilization. Four experimental groups were designed including; normal eggs as control group and sperms without UV thermal shock), gynogenesis (Sperm irradiated with UV and thermal shock were applied), triploid (thermal shock without radiation by UV on sperm) and haploid group (without thermal shock but using irradiated sperm for fertilization). Verification of the success of treatments was assessed using genetic analysis on sturgeon larvae and fingerlings. In triploids the total surface area, volume of cells and nucleus as well as chromosome number were determined. To identify a gynogenetic larva, microsatellite markers were used to analysis specific loci by using primers designed for lake ...